Genetic and clinical landscape of Duchenne muscular dystrophy in Guatemala: insights from a national study - Orozco, M.; Kestler, E.; Ramirez, G.; Silva, G.; Cabrera, J.; De la Vega, S.; Al Khleifat, A. (Frontiers in Genetics, 2025)
Duchenne muscular dystrophy (DMD) is a severe X-linked disorder caused by mutations in the DMD gene, and it has a global prevalence of 3.6 per 100,000 people. Despite its well-documented genetic basis, no previous studies have characterized DMD in Guatemala. We analyzed 33 genetically confirmed cases to estimate the prevalence, describe the mutation spectrum, and assess the clinical features. The prevalence was 0.61 per 100,000 men younger than 30 years. Symptoms began before the age of 5 years in 85% of cases, yet 60% cases were diagnosed after the age of 6 years, highlighting significant diagnostic delays. Deletions were the most common mutation (55%), followed by point mutations (30%) and duplications (15%), with two novel variants being identified. Most deletions clustered in the exon 45–55 hotspot. Nearly half of the cases were eligible for exon-skipping therapies. These findings reveal genetic heterogeneity in the Guatemalan population, substantial delays in diagnosis, and the need for improved access to genetic testing, targeted treatments, and a national DMD registry.